Wind Power Ramps Analysis for High Shares of Variable Renewable Generation in Power Systems - Mohammed Saber Eltohamy; Mohammed Said Abdel Moteleb; Hossam Talaat; Said Fouad Mekhemar; Walid Omran (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
Power system operators should be provided with more information on the characteristics of variable generation power ramps because, although there has been an improvement in the forecasting of wind power, the percentage of error in forecasting is still high to some extent. As a result of the ongoing rise in the participation rate of variable generation, this error will have a significant impact on the balance of power generation and consumption. From the grid operators' viewpoint, in order to balance these ramp events, it is important to get the scale of ramp events in the system as well as the times during which collective events are most likely to arise in order to achieve flexibility and reliability in the power system. Digitization of power systems brings big data which opening opportunities for improving the efficiency of power system operation. This paper analyzes the historical data of power-time curve in two directions: vertical and horizontal, in order to gain details on the behavior of wind power ramps. The method of analysis will be demonstrated by an analysis of actual historical output power of aggregated Belgian wind farms every 15 minutes in 2017 and 2018. Comparing the results of the two years outlined that there are fixed percentages related to wind power ramping behavior and even if the wind capacity is increased, it is possible to determine the extent of these ramps.